Intersubjectivity and historicity: contributions from modern hermeneutics to ethnographic research (Revista Latino-Americana de Enfermagem, 2002)
Considering the large penetration of the hermeneutic paradigm in contemporary social research, this article proposes the reflection on some of its theoretical and methodological assumptions which can be trussed under the categories "intersubjectivity" and "historicity".